Responsible Leadership: Global and Contextual Ethical Perspectives - Sibomana, Juvenal (Journal of Dharma, 2011)
This book, co-edited by Stiickelberger and Mugambi, is very enriching as it offers formative orientations and strategies about the responsible leadership in a global context. It is a collection of 39 contributions (speeches and papers) from 21 countries which were presented in the conference organised by Globethics.net (September 2005), whose founder and executive director is Stiickelberger himself. The authors are scholars in applied ethics, ethicists and practitioners from different continents. According to the editors, "All authors are rooted in their own context and try, at the same time, to overcome it in situations of transformation and to confront it with global challenges" (2); hence, their contributions are rich, fascinating, innovative, and open towards new global perspectives about responsible leadership and good governance.